Extracellular vesicles mediate intercellular communication: Transfer of functionally active microRNAs by microvesicles into phagocytes. Issue 9 (20th July 2017) - Claßen, Laura; Tykocinski, Lars‐Oliver; Wiedmann, Felix; Birr, Carolin; Schiller, Petra; Tucher, Christine; Krienke, Stefan; Raab, Marc‐Steffen; Blank, Norbert; Lorenz, Hanns‐Martin; Schiller, Martin
Abstract : We systematically characterized different types of extracellular vesicles. Microvesicles released from viable or apoptotic lymphocytes carry a stimulus dependent composition of different miRNA. These microvesicles are engulfed by monocytes and carry functionally active miR‐155 to recipient cells. MiRNA composition of microvesicles differs between SLE patients and healthy controls. Abstract: Cell activation and apoptosis lead to the formation of extracellular vesicles (EVs) such as exosomes or microvesicles (MVs). EVs have been shown to modulate immune responses; recently, MVs were described to carry microRNA (miRNA) and a role for MVs in the pathogenesis of autoimmune diseases has been discussed. Here we systematically characterized MVs and exosomes according to their release stimuli. The miRNA content of viable or apoptotic human T lymphocytes and the corresponding MVs was analyzed. miRNA, protein and surface marker expression, as well as cytokine release by human monocytes was measured after EV engulfment. Finally, miRNA expression in T lymphocytes and MVs of healthy individuals was compared with those of systemic lupus erythematosus (SLE) patients. We demonstrate that, depending on the stimuli, distinct subtypes of EVs are released, differing in size and carrying a specific RNA profile. We observed an accumulation of distinct miRNAs in MVs after induction of apoptosis and the transfer of functional miRNA by MVs into human monocytes. MVs released from apoptotic cells provoke less of an inflammatory response than those released from viable cells. MiR‐155*, miR‐34b and miR‐34a levels in T lymphocytes and corresponding MVs were deregulated in SLE when compared to healthy individuals.